Red blood cell proteomics reveal remnant protein biosynthesis and folding pathways in PIEZO1-related hereditary xerocytosis - Caulier, Alexis; Jankovsky, Nicolas; Gautier, Emilie Fleur; El Nemer, Wassim; Guitton, Corinne; Ouled-Haddou, Hakim; Guillonneau, François; Mayeux, Patrick; Salnot, Virginie; Bruce, Johanna; Picard, Véronique; Garçon, Loïc (Frontiers in Physiology, 2022)
Hereditary xerocytosis is a dominant red cell membrane disorder characterized by an increased leak of potassium from the inside to outside the red blood cell membrane, associated with loss of water leading to red cell dehydration and chronic hemolysis. 90% of cases are related to heterozygous gain of function mutations in PIEZO1, encoding a mechanotransductor that translates a mechanical stimulus into a biological signaling. Data are still required to understand better PIEZO1-HX pathophysiology. Recent studies identified proteomics as an accurate and high-input tool to study erythroid progenitors and circulating red cell physiology. Here, we isolated red blood cells from 5 controls and 5 HX patients carrying an identified and pathogenic PIEZO1 mutation and performed a comparative deep proteomic analysis. A total of 603 proteins were identified among which 56 were differentially expressed (40 over expressed and 16 under expressed) between controls and HX with a homogenous expression profile within each group. We observed relevant modifications in the protein expression profile related to PIEZO1 mutations, identifying two main “knots”. The first contained both proteins of the chaperonin containing TCP1 complex involved in the assembly of unfolded proteins, and proteins involved in translation. The second contained proteins involved in ubiquitination. Deregulation of proteins involved in protein biosynthesis was also observed in in vitro-produced reticulocytes after Yoda1 exposure. Thus, our work identifies significant changes in the protein content of PIEZO1-HX erythrocytes, revealing a “PIEZO1 signature” and identifying potentially targetable pathways in this disease characterized by a heterogeneous clinical expression and contra-indication of splenectomy.